Potential hypoglycemic effect of acetophenones from the root bark of Cynanchum wilfordii. Issue 16 (18th August 2019) - Jiang, Hao-Wen; Gu, Shan-Shan; Cao, Lei; Jiang, Sheng-Shi; Lin, Jing; Chen, Yan; Wang, Ling; Jiao, He; Li, Jing-Ya; Zhao, Wei-Min; Li, Jin-Long
Abstract: Three new acetophenones, named cynwilforones A–C (1 –3 ), together with cynandione A (4 ) were isolated from the root bark of Cynanchum wilfordii (Maxim.) Hemsl. Their structures were deduced based on spectroscopic analysis and chemical methods. Compounds1 and4 exhibited potential hypoglycemic effects through inhibition of hepatic gluconeogenesis by down-regulating the expression of phosphoenolpyruvate carboxykinase and glucose-6-phosphatase. This is the first report that acetophenones from the root bark of C. wilfordii possesses potential hypoglycemic activity in vitro . Abstract :